Priority problems in occupational hygiene and safety of medical workers in emergency situations (from the experience of overcoming the Covid-19 pandemic) (Environment & Health, 2024)
Introduction. The working conditions of medical personnel during emergencies significantly differ from those in regular circumstances. During the COVID-19 pandemic, the intensity of biological and psychophysiological factors in the working environment increased substantially, leading to the emergence of additional harmful and dangerous factors, resulting in disruptions to the living and working conditions of the staff. Since the regular work routine of healthcare facilities changes in such situations, there is a pressing need for clear action plans and guidelines to provide quality medical care and safeguard the lives and health of medical workers.The aim of this study is to examine the experience of medical facilities during the COVID-19 pandemic, investigate the impact of working conditions during quarantine and the resolution of dangerous situations, substantiate safety measures, and establish guidelines for the behavior of medical personnel and patients during other potential emergencies.Materials and Methods. The research was conducted using questionnaire, survey, hygienic, bibliographic and statistical methods.Results. Peculiarities of the labor activity of medical workers in health care facilities during the COVID-19 pandemic, which was recognized as a particularly dangerous disease, and the working conditions of personnel in these conditions were studied. An analysis of the perception of medical workers during the pandemic and the evaluation of working conditions were conducted. The main negative effects on the working conditions of healthcare staff compared to the pre-pandemic period were identified: increased workload and demands on workers, growing emotional stress, insufficient organizational support, financial, and psychological assistance. Additionally, positive influences that eased the tasks of the medical workers during the COVID-19 pandemic and contributed to stabilizing the situation and personal and professional development were highlighted: competence, cooperation, and team cohesion (teamwork). Respondents stated that the acquired experience would prevent them from making numerous mistakes and shortcomings in their work in the future, and they are ready to work under epidemic conditions and other emergencies. To ensure the safety of medical personnel, it is necessary to implement comprehensive measures to prevent occupational diseases, care for human resources, and develop reward and motivation systems. To improve the quality of medical services during emergencies, reduce risks among patients, and safeguard the lives and health of medical workers, mandatory targeted training programs and educational materials are required for preparing healthcare personnel for work in different emergency situations.Conclusions. The working conditions of medical personnel during the fight against the coronavirus infection are hazardous, posing threats to their lives and carrying a high risk of acute occupational diseases and severe forms of illnesses, including death. The main negative influences on the working conditions of healthcare staff include workload, emotional stress, and inadequate organizational support and assistance. Positive effects that facilitated the work of medical during the COVID-19 pandemic were also highlighted: competence, cooperation and cohesion (teamwork), which contributed to the stabilization of the situation in health care facilities, individual and professional development of medical workers. Therefore, it is crucial to create mandatory targeted training programs and educational materials for healthcare personnel to prepare them to work in different emergency situations effectively.
Keywords: medical workers; COVID-19 pandemic; workload; emotional stress; organizational support; competence; cooperation; prevention; safety training